Implications of Round Bale Dimensions on Hay Use - Matt Hersom; Todd Thrift; Joel Yelich (EDIS)
The dimensions of large round bales make a difference in many cases. Bale size determines the amount of hay in a purchased bale, the amount of nutrients in pounds, and the extent of spoilage during storage and feeding. Large round bales, the predominant form of hay made and fed to cattle, are under discussion. This 3-page fact sheet is a new document that examines the significance of bale dimensions, volume, density, and weight as well as the relationship of these factors to hay prices. Written by Matt Hersom, Todd Thrift, and Joel Yelich, and published by the UF Department of Animal Sciences, June 2016.